Pengkajian Ilmu-Ilmu Sosial: Menuju ke Pembentukan Konsep Tepat - Syed Farid Alatas (Antropologi Indonesia, 2003)
While there has been awareness of the problems of the relevance of Western concepts, theories and assumptions in critical works on the state of the social sciences in the Third World, what is meant as a conceptual level by relevance and irrelevance has rarely been the subject of discussion. The conceptualization of relevance is important because it lies at the basis of efforts to make the social sciences more relevant to conditions in the Third World. Nevertheless, the calls for greater relevance have generally been made in vague terms owing to the less than systematic manner in which "irrelevance" was discussed. The result was that calls for more relevant social sciences were equally unclear. This paper aims to advance our understanding of the problem of relevance by way of providing a preliminary conceptualization of relevance.